2019
DOI: 10.3847/1538-4357/ab5716
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Nonaxisymmetric Features of Virgo Cluster Early-type Dwarf Galaxies. II. Tidal Effects on Disk Features and Stability

Abstract: A fraction of dwarf galaxies in the Virgo cluster contain disk features like bars and spiral arms. Using N -body simulations, we investigate the effects of tidal forces on the formation of such disk features in disk dwarf galaxies resembling VCC856. We consider 8 Cluster-Galaxy models in which disk dwarf galaxies with differing pericenter distance and spin orientation experience the tidal gravitational force of a Virgo-like NFW halo, and additional 8 Galaxy-Galaxy models in which two dwarf galaxies undergo tid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Mastropietro et al (2005a) showed that, due to tidal interactions, asymmetric features and open spiral arms can be formed in those dEs which are located in the outskirts of cluster. In addition to that and as shown by Kwak et al (2019), the cluster tidal field can trigger the formation of weak spiral arms in disk dEs. These results might explain the existence of the faint spiral arms in VCC1896.…”
Section: Stellar Rotation In Vcc0608 and Vcc1896supporting
confidence: 52%
See 1 more Smart Citation
“…Mastropietro et al (2005a) showed that, due to tidal interactions, asymmetric features and open spiral arms can be formed in those dEs which are located in the outskirts of cluster. In addition to that and as shown by Kwak et al (2019), the cluster tidal field can trigger the formation of weak spiral arms in disk dEs. These results might explain the existence of the faint spiral arms in VCC1896.…”
Section: Stellar Rotation In Vcc0608 and Vcc1896supporting
confidence: 52%
“…Tidal interactions are known as one of the most dominant mechanisms that can induce instabilities in the stellar disk of galaxies and form bars, particularly in central regions of galaxy clusters and groups . Moreover, Kwak et al (2019) showed that tidal effects due to galaxy-galaxy interactions, which are more dominant in the central parts of a cluster, can be efficient in causing instabilities to bar formation in dwarf galaxies in a Virgo-like halo. As for Virgo, observations of Janz et al ( 2012) also confirm that dEs with bars are mostly observed in the central parts of the cluster.…”
Section: Stellar Rotation In Vcc0608 and Vcc1896mentioning
confidence: 99%
“…We note that spiral structure in intermediate mass disk galaxies in cluster environments may result from tidal forces (e.g. Kwak et al 2019). While not classified as a dwarf SO, Lisker et al (2006a) conclude that NGC 4306 has a 'certain disk', with integrated colors and a luminosity that are similar to those of the other five galaxies.…”
Section: A Sample Of Early-type Intermediate Mass Disk Galaxies In Virgomentioning
confidence: 78%
“…Since the buckling instability deforms the disk in the vertical direction, it naturally involves an asymmetry in the vertical velocities of disk particles. One way to quantify the onset and strength of the buckling instability is to monitor the evolution of |〈v z 〉|, where the angle brackets denote the spatial average at R = 2 kpc (Kwak et al 2017(Kwak et al , 2019. Figure 15 plots |〈v z 〉| against time for all models.…”
Section: Buckling Instabilitymentioning
confidence: 99%